2023
DOI: 10.1039/d2na00733a
|View full text |Cite
|
Sign up to set email alerts
|

Capturing charge and size effects of ions at the graphene–electrolyte interface using polarizable force field simulations

Abstract: We present a systematic investigation capturing the charge and size effects of ions interacting with the graphene surface using polarizable simulations. Our results utilizing the Drude polarizable force field (FF)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, in Drude polarizable FF simulations, the graphene surface is able to respond to changes in the local environment, specifically the negative charge on the phosphate, leading to the accurate capture of both vdW and electrostatic interactions between the dimethyl phosphate molecule and the graphene surface. Drude polarizable simulations were able to capture similar interactions between the negatively charged Cl – ion and the graphene surface, which could not be captured by additive (nonpolarizable) simulations . Using batch adsorption experiments, Vasudevan and Lakshmi have shown that graphene has excellent phosphate adsorption properties .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in Drude polarizable FF simulations, the graphene surface is able to respond to changes in the local environment, specifically the negative charge on the phosphate, leading to the accurate capture of both vdW and electrostatic interactions between the dimethyl phosphate molecule and the graphene surface. Drude polarizable simulations were able to capture similar interactions between the negatively charged Cl – ion and the graphene surface, which could not be captured by additive (nonpolarizable) simulations . Using batch adsorption experiments, Vasudevan and Lakshmi have shown that graphene has excellent phosphate adsorption properties .…”
Section: Resultsmentioning
confidence: 99%
“…Drude polarizable simulations were able to capture similar interactions between the negatively charged Cl − ion and the graphene surface, which could not be captured by additive (nonpolarizable) simulations. 39 Using batch adsorption experiments, Vasudevan and Lakshmi have shown that graphene has excellent phosphate adsorption properties. 66 They observed that the interaction of phosphate with the graphene surface was highly endothermic and a spontaneous process.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 3 more Smart Citations